EFFICACY OF ORAL GLUTATHIONE ADDITION IN LUTEIN SUPPLEMENTATION ON CONTRAST SENSITIVITY IMPROVEMENT IN DRY AGE-RELATED MACULAR DEGENERATION: A RANDOMIZED CONTROLLED TRIAL - AMIN, RAMZI; SAPUTRA, EDWIN BAYU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Age-related macular degeneration (ARMD) is the macular abnormality causing central vision loss in the elderly. One prevention for ARMD is the provision of antioxidants, such as lutein. Reduced form of glutathione (GSH) is a source of cysteine and sulfhydryl, playing a role in detoxification, transport, and metabolic processes. Both are prospected to have a synergistic effect in the prevention of ARMD. This study aimed to determine the efficacy of GSH addition in lutein supplementation to improve the contrast sensitivity of dry type ARMD patients. Methods: This randomized controlled trial was conducted at an eye hospital and a tertiary general hospital from April 2016 to June 2016. This study involved 22 dry ARMD patients. Subjects were randomized and divided into treatment groups with 20 mg lutein with the addition of 500 mg GSH and 20 mg lutein only, for 30 days. Contrast sensitivity measurement was performed with Lea Numbers® Low Contrast Flip Chart before and after the treatment. Contrast sensitivity was analyzed comparatively with paired t-test. Results: Contrast sensitivity improvement was observed in both the groups. Contrast sensitivity improvement of the group with additional GSH (3.62±1.44, p<0.05) was a 3-fold of the lutein group only (1.25±0.44, p>0.05). The result was statistically significant for the group treated with GSH addition. Conclusion: GSH addition in lutein supplementation provoked better contrast sensitivity improvement in dry ARMD patients.